Observation of the Leptonic Decay D+ ??+?? - Çetin, Serkant Ali (American Physical Society, 2019)
We report the first observation of D+??+?? with a significance of 5.1?. We measure B(D+??+??)=(1.20±0.24stat±0.12syst)×10-3. Taking the world average B(D+??+??)=(3.74±0.17)×10-4, we obtain R?/?=?(D+??+??)/?(D+??+??)=3.21±0.64stat±0.43syst., which is consistent with the standard model expectation of lepton flavor universality. Using external inputs, our results give values for the D+ decay constant fD+ and the Cabibbo-Kobayashi-Maskawa matrix element |Vcd| that are consistent with, but less precise than, other determinations.